Testing Company Size as a Moderation Variable on the Influence of Asset Structure and Growth on Capital Structure - Ayem, Sri; Agustina, Cindy Alfira (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This study aims to examine the role of company size in moderating the influence of asset structure and asset growth on capital structure. The research was conducted on financial companies listed on the IDX for the 2018-2023 period, using quantitative methods and purposive sampling techniques, with a total sample of 26 companies. Data analysis uses Moderated Regression Analysis (MRA). The results show that asset structure and asset growth have a significant effect on capital structure. In addition, the size of the company is able to moderate the influence of asset structure and asset growth on capital structure. The implications of this study show that companies need to consider asset structure, asset growth, and company size to optimize capital structure decisions and minimize financial risks.